In Vivo Pharmacodynamic Activities of Two Glycylcyclines (GAR-936 and WAY 152,288) against Various Gram-Positive and Gram-Negative Bacteria (2000)
ABSTRACT: The in vivo pharmacodynamic activities of two glycylcyclines (GAR-936 and WAY 152,288) were assessed in an experimental murine thigh infection model in neutropenic mice. Mice were infected with one of several strains of Streptococcus pneumoniae, Staphylococcus aureus, Escherichia coli, or Klebsiella pneumoniae. Most infections were treated with a twice-daily dosing schedule, with administration of 0.75 to 192 mg of GAR-936 or WAY 152,288 per kg of body weight. A maximum-effect dose-response model was used to calculate the dose that produced a net bacteriostatic effect over 24 h of therapy. This dose was called the bacteriostatic dose. More extensive dosing studies were performed with S. pneumoniae 1199, E. coli ATCC 25922, and K. pneumoniae ATCC 43816, with doses being given as one, two, four, or eight equal doses over a period of 24 h. The dosing schedules were designed in order to minimize the interrelationship between the various pharmacokinetic and pharmacodynamic parameters studied. These parameters were time above 0.03 to 32 times the MIC, area under the concentration-time curve (AUC), and maximum concentration of drug in serum (Cmax). The bacteriostatic dose remained essentially the same, irrespective of the dosing frequency, for S. pneumoniae 1199 (0.3 to 0.9 mg/kg/day). For E. coli ATCC 25922 and K. pneumoniae ATCC 43816, however, more frequent dosing led to lower bacteriostatic doses. Pharmacokinetic studies demonstrated dose-dependent elimination half-lives of 1.05 to 2.34 and 1.65 to 3.36 h and serum protein bindings of 59 and 71% for GAR-936 and WAY 152,288, respectively. GAR-936 and WAY 152,288 were similarly effective against the microorganisms studied, with small differences in maximum effect and 50% effective dose. The glycylcyclines were also similarly effective against tetracycline-sensitive and tetracycline-resistant bacteria. Time above a certain factor (range, 0.5 to 4 times) of the MIC was a better predictor of in vivo efficacy than Cmax or AUC for most organism-drug combinations. The results demonstrate that in order to achieve 80% maximum efficacy, the concentration of unbound drug in serum should be maintained above the MIC for at least 50% of the time for GAR-936 and for at least 75% of the time for WAY 152,288. The results of these experiments will aid in the rational design of dose-finding studies for these glycylcyclines in humans.